Environmental Law Enforcement: A Reevaluation - Stephen Adi Odey (dialektika kontemporer, 2023)
Environmental deterioration has continued to pose severe difficulties for Nigeria's health and economic growth. Deforestation, pollution, global warming, and inappropriate pesticide use are a few of these issues. Nigeria appears to be in a degenerative state despite environmental laws and policies aimed at improving these issues since these regulations are not properly implemented. This essay examines how several Nigerian enforcement organisations apply environmental regulations, the strategies they employ, and the difficulties they have in upholding the pertinent legislation. The low-level environmental protection provisions in the constitution, the roles and disputes in environmental management, the courts' excessive commitment to legalism, and the lack of information disclosure requirements are some of these difficulties. Therefore, the legislative goals are not met because of the following: insufficient punishment for noncompliance; insufficient time between noncompliance and enforcement; inadequate compensation for injured parties; and administrative rather than criminal or remedial measures for certain environmental crimes. The report promotes the formation of environmental courts, the emergence of environmental crises, the development of processes to increase public engagement in Nigerian environmental protection, and the encouragement of litigation in the public and private interest.